The Time Fractional Schrödinger Equation with a Nonlinearity of Hartree Type - Prado-Castillo, H (Birkhauser, 2021)
The aim of this work is to show existence, uniqueness and regularity properties of local in time mild solutions for the nonlinear space-time fractional Schrödinger equation (1.1), with a fractional time derivative of order α∈ (0 , 1) , and with a nonlinear term of Hartree type. © 2021, Springer Nature Switzerland AG.
Keywords: Time fractional Schrodinger equation; Caputo fractional derivative; Fractional Laplace operator; Fractional-order Sobolev space; Hartree-type nonlinearity